High performance long-distance running - Sunderland, David (The Crowood Press, 2011)
High Performance Long Distance Running" is a book for long-distance runners (5,000 metres to the Marathon) and their coaches. The book is practically based on sound principles, which have been tried and tested repeatedly. Progression, planning, preparation and peaking are all important parts of the complete performance